MODEL PEMBELAJARAN YANG AKTIF, KREATIF, EFEKTIF, DAN MENYENANGKAN (PAKEM) - Istiyanti, Istiyanti (Universitas Muhammadiyah Magelang, 2011)
In learning with teachers PAKEM conditioned active learning situations, creative, effective and fun. To support this learning can be used angsung learning models, cooperative, and prolem-based learning. Learning with the direct model is specifically designed to support student learning with respect to procedural knowledge and knowledge of well-structured and can be studied step by step.Cooperative learning merupkan learning model that promotes cooperation among students to achieve learning goals. This type of cooperative learning include STAD, Jigsaw, and TGT. The steps, namely: To complete the learning material students learn in cooperative groups. Dadri formed group of students who have high ability, medium and weak. The award is closer to the working group of the individual.Model-Based Learning Problen study aims to: help students develop thinking skills and problem solving skills; Studying the role of adults who are authentic; Being an independent learner.